1992
DOI: 10.1136/bmj.305.6864.1249
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture in fibromyalgia: results of a controlled trial.

Abstract: Objective-To determine the efficacy of electroacupuncture in patients with fibromyalgia, a syndrome of unknown origin causing diffuse musculoskeletal pain.Design-Three weeks' randomised study with blinded patients and evaluating physician.Setting-University divisions of physical medicine and rehabilitation and rheumatology, Geneva.Patients-70 patients (54 women) referred to the division for fibromyalgia as defined by the American College of Rheumatology.Interventions-Patients were randomised to electroacupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
201
2
24

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 266 publications
(229 citation statements)
references
References 26 publications
2
201
2
24
Order By: Relevance
“…Four studies could be combined in an analysis regarding the immediate treatment effect [22,37,49,93], and two studies were analyzed regarding longterm effects of acupuncture in pain conditions [49,52]. The results of these metaanalyses confirm our descriptive findings.…”
Section: Meta-analysissupporting
confidence: 71%
See 4 more Smart Citations
“…Four studies could be combined in an analysis regarding the immediate treatment effect [22,37,49,93], and two studies were analyzed regarding longterm effects of acupuncture in pain conditions [49,52]. The results of these metaanalyses confirm our descriptive findings.…”
Section: Meta-analysissupporting
confidence: 71%
“…Nine of these reported the PPT to be significantly elevated [33,40,41,43,51,64,78,79,83], and one study found no significant PPT increase [50]. Among the 26 studies (74.3%) that assessed the effectiveness of an acupuncture series, 18 (69.2%) showed a PPT increase after treatment [37,38,46,50,52,62,63,68,70,72,74,77,81,82,86,87,91,93] while six studies (23.1%) observed no effect of acupuncture on the PPT [22,27,[47][48][49]96]. The outcome of two studies was rated as unclear, because the analysis was performed by combining data of all groups [44,45].…”
Section: Ppt Assessed In Pain Disordersmentioning
confidence: 99%
See 3 more Smart Citations